Side chain engineering in π-stacked polybenzofulvene derivatives bearing electron-rich chromophores for OLED applications. Issue 123 (24th November 2015) - Cappelli, Andrea; Razzano, Vincenzo; Fabio, Giuseppe; Paolino, Marco; Grisci, Giorgio; Giuliani, Germano; Donati, Alessandro; Mendichi, Raniero; Mróz, Wojciech; Villafiorita-Monteleone, Francesca; Botta, Chiara
Abstract : Side chain engineering designed to introduce electron donating chromophores in the 3-phenylindene scaffold led to the discovery of a highly emissive polybenzofulvene derivative for OLED applications. Abstract : In order to obtain new polymeric materials endowed with improved optoelectronic performances, suitable side chain engineering was designed to insert different chromophores showing electron donating ability [ i.e. triphenylamine (TPA) and 9-methylcarbazole (MCBZ) residues] in two different key positions ( i.e. 6 and 4′) of the 3-phenylindene scaffold of the polybenzofulvene monomeric units. Among the four newly-synthesized polybenzofulvene derivatives, those bearing triphenylamine moieties were found to show higher emissive properties with respect to the corresponding carbazole derivatives. Moreover, the preliminary OLED devices prepared with the triphenylamine-based polymers showed promising features, but the role of the aggregation process in affecting the emission properties of poly-6-TPA-BF3k suggested that extensive device development studies are required in order to maximize polybenzofulvene performances in OLED applications.